Russian colonial society in Tashkent : 1865-1923 - Sahadeo, Jeff, 1967- (Indiana University Press, 2007)
This intensively researched urban study dissects Russian Imperial and early Soviet rule and colonial society in Islamic Central Asia from the viewpoints of tsarist functionaries, soviet bureaucrats, Russian workers, lower-class women as well as Muslim notables and Central Asian traders.